What contextual factors influence pain management decision making concerning player availability in professional men`s football? A qualitative analysis of practitioner perceptions - Read, D.; Rosenbloom, C. (Science and Medicine in Football, 2025)
Purpose: Football practitioners must regularly assess the risk of participation when determining player availability. At present, there is a lack of information detailing the factors that influence risk assessments. Accordingly, the following research question was explored: what contextual factors influence pain management decision-making when determining player availability in professional men`s football? Methods: 20 semi-structured interviews were conducted with club doctors (8), physiotherapists (6), and heads of medicine and performance (8) working in professional men`s football in the United Kingdom. The methodology is reported using COREQ criteria and data were analysed using thematic analysis. Results: Three themes were created that explain how decision-making concerning analgesia was influenced by: (1) access to medical resources, (2) trust between staff and players, and (3) prioritising short-term success. First, the time, resources, and medical information available to staff impacted the ability to assess players and their risk tolerance in relation to analgesia. Second, decision-making was perceived as a multi-stakeholder process and the nature of relationships with players and performance staff could increase or decrease risk tolerance. Third, player decisions are made against a performance and working environment that privileges short term success over long term wellbeing. Conclusion: The data support that pain management decision-making in professional men`s football is influenced by the player and staff`s working context. Further, practitioners viewed potential harm to a player from a socio-economic and physical perspective. These findings support the adoption of a patient-centred care approach and can inform clear recommendations from international and national governing bodies.